Assessing pharmacists’ readiness to prescribe oral antibiotics for limited infections using a case-vignette technique - Ung, E.; Czarniak, P.; Sunderland, Bruce; Parsons, Richard; Hoti, Kreshnik (Springer Netherlands, 2017)
Background: Pharmacist’s skills are underutilized whilst they are directly involved with antibiotic supply to the community. Addressing this issue could lead to better use of antibiotics and hence decreased resistance. Objective Explore how pharmacists can prescribe oral antibiotics to treat a limited range of infections whilst focusing on their confidence and appropriateness of prescribing. Setting Community pharmacies, Western Australia. Method Data were collected using a self-administered questionnaire also containing case vignettes. These were distributed to a random sample of metropolitan and rural community pharmacies in Western Australia. A Generalised Estimating Equation was used to compare respondents’ level of confidence in treating various infections and to assess appropriateness of prescribing. Main outcome measure Appropriateness and confidence of antibiotic prescribing. Results A response rate of 34.2% (i.e. 425 responses to case vignettes) was achieved from 240 pharmacies. There were high levels of confidence to treat simple infections such as uncomplicated UTIs (n = 73; 89.0%), impetigo (n = 65; 79.3%), mild bacterial skin infections (n = 62; 75.6%) and moderate acne (n = 61; 72.4%). Over 80% of respondents were confident to prescribe amoxicillin (n = 73; 89%), trimethoprim (n = 72; 87.8%), amoxicillin and clavulanic acid (n = 70; 85.4%), flucloxacillin (n = 70; 85.4%) and cephalexin (n = 68; 82.9%). High levels of appropriate antibiotic prescribing were shown for uncomplicated UTI (97.2%), cellulitis (98.2%) and adolescent acne (100.0%). Conclusion This study identified key limited infections and antibiotics for which pharmacists were supportive and confident to prescribe. This role could lead to better use of antibiotics in the community and minimisation of resistance.